PERANCANGAN SISTEM INFORMASI PENJUALAN MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT (RAD) DI PABRIK GENTENG UUN SUPER JATIWANGI - Wawan Ridwan Kusaeri; Puji Juliana; Rivaldi Rizki Pratama (Prosiding Semnastek, 2018)
The sales that have been used by tile manufacturers are by collaborating with several selling agents to market various types of tiles. Sales in this way require a long time in the process of selling these products, so this system is considered less effective and efficient. if it only relies on this method, the tile factory revenue will not experience a significant increase. In addition, the development of the tile factory feels rather slow. therefore, a sales information system is designed that aims to minimize shipping process time with the aim of increasing sales volume so that tile factory revenue can increase. The tile sales information system is designed with a laravel framework, bootstrap and using XAMPP. Sales information systems using bootstrap at tile factories are built as information media that can assist in the sales process and delivery.